Memorandum of understanding between Universiti Teknologi MARA and Samara National Research University / Fakulti Kejuruteraan Mekanikal - Universiti Teknologi MARA, Fakulti Kejuruteraan Mekanikal (Universiti Teknologi MARA (UiTM), 2021)
UiTM and Samara National Research University will endeavour to strengthen, promote and develop cooperation on the basis of equality and mutual benefit.